GSK-3 Inhibitors and Tooth Repair: An Ethical Analysis - Hostiuc, Sorin; Perlea, Paula; Marinescu, Mihai; Dogaroiu, Catalin; Drima, Eduard (Frontiers in Pharmacology, 2019)
Tideglusib®, a GSK-3 inhibitor, was initially tested for the treatment of Alzheimer’s disease. However, a recent report has suggested its potential off-label use for the treatment of dental cavities. Even if this effect is not yet confirmed, this off-label use can have significant public/dental health consequences, mainly because of the large number of patients with cavities. The purpose of this mini-review is to perform an ethical analysis of the use of Tideglusib in dentistry. The ethical analysis identified three main areas in which ethical breaches could be significant: 1) respect for the autonomy of the patient, 2) issues raised by horizontal shifts in the translational research process, and 3) the conflict between dental beneficence and general non-maleficence. In conclusion, the use of Tideglusib in dentistry should respect the same strict ethical and regulatory criteria from clinical medicine. A translation of the potential risks should be done only after large-scale, phase-III/IV clinical trials, explicitly designed to test the usefulness of this drug in dental medicine.